Desarrollo de una aplicación web y móvil para la gestión de inventarios y ventas de la Asociación Producción Alimenticia Nueva Esperanza. - Guilcazo Toapanta, Geomaira Belen (2021)
The objective of every company, association or organization is to generate sales, which is why the Nueva Esperanza Food Production Association must be at the forefront of technological advances. Thus seeking to maintain an updated inventory of the dairy products it offers, its real financial statements avoiding economic losses, thus seeking to obtain confidence in the payments made to raw milk suppliers through the use of a mobile application. On the other hand, this project is focused on finding alternatives or technological resources that help promote and market the products that are made, generating sales to the association. Currently the association has technological resources (computer, internet and smart cell phone) that help the implementation of the web and mobile application, for this it is necessary that the association contract services such as hosting and an account in Play Store to be way to maintain online services, thus allowing them to promote the products they offer, manage inventories of finished products and sales, as well as the recording of information on raw milk by producers. The development team has adequate knowledge of web application development, software management such as: PHP, Laravel, MySQL database manager. For the mobile application, the JAVA programming language and the Android Studio platform. The development of this project is important because it allows to improve the processes carried out by the Nueva Esperanza Food Production Association, allowing its products to be known through the use of technology.